2016
DOI: 10.1037/pas0000217
|View full text |Cite
|
Sign up to set email alerts
|

The importance of assessing clinical phenomena in Mechanical Turk research.

Abstract: Amazon.com's Mechanical Turk (MTurk) website provides a data collection platform with quick and inexpensive access to diverse samples. Numerous reports have lauded MTurk as capturing high-quality data with an epidemiological sample that is more representative of the U.S. population than traditional in-person convenience samples (e.g., undergraduate subject pools). This benefit, in combination with the ease and low-cost of data collection, has led to a remarkable increase in studies using MTurk to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
215
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(242 citation statements)
references
References 42 publications
22
215
5
Order By: Relevance
“…A growing body of literature has examined the prevalence of internalizing symptoms and disorders in MTurk samples, yielding conflicting results. Whereas some findings have suggested that MTurk workers report higher rates of depression and anxiety symptoms than do community sample participants (Arditte et al., ), other studies have suggested either comparable (Shapiro, Chandler, & Mueller, ) or lower (Veilleux, Salomaa, Shaver, Zielinsky, & Pollert, ) levels of such symptoms in MTurk samples.…”
Section: Discussionmentioning
confidence: 97%
“…A growing body of literature has examined the prevalence of internalizing symptoms and disorders in MTurk samples, yielding conflicting results. Whereas some findings have suggested that MTurk workers report higher rates of depression and anxiety symptoms than do community sample participants (Arditte et al., ), other studies have suggested either comparable (Shapiro, Chandler, & Mueller, ) or lower (Veilleux, Salomaa, Shaver, Zielinsky, & Pollert, ) levels of such symptoms in MTurk samples.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, although our sample provided a broader perspective on this association than samples of undergraduate students or patients with a particular disorder, our findings may not be generalizable to more specific populations, particularly high‐risk groups such as psychiatric inpatients. Moreover, although this study was intended to capture a representative community sample, recent research indicates that MTurk participants may have higher rates of social anxiety and depression than the general population (Arditte et al., ; Shapiro et al., )—and therefore may also have higher than average rates of suicidality. Although we were unable to examine these constructs in the present sample, it is possible that the self‐selective and voluntary nature of MTurk participation altered our findings—given that this study was presented as a study examining “diet, exercise, personality, and mental health.” As such, this study may not be truly representative of the general community, although it is certainly more representative than studies of undergraduate students or psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were recruited through Amazon's Mechanical Turk, an online method of accessing a large participant pool by posting tasks online and providing monetary compensation for their completion (MTurk; Buhrmester, Kwang, & Gosling, 2011). Recent findings suggest that MTurk has a higher percentage of individuals with clinical depressive symptomatology compared to the general population (approximately 32%; Arditte, C ß ek, Shaw, & Timpano, 2016). Of those at or above the clinical cutoff score of 14 on the depression inventory used in the study, 53 reported mild, 50 reported moderate, and 32 reported severe symptomatology (M depression = 23.51, SD depression = 8.78).…”
Section: Methods Participantsmentioning
confidence: 99%